Doped copper compound desulfurizing agent as well as preparation method and application thereof

By using chlorine-doped copper composite as a desulfurizer, the reaction of copper chloride and metal powder is used to form a chlorine-doped copper composite, the problem of slowing down the vulcanization rate and the vulcanization reaction of the existing copper oxide desulfurizer is solved, and high sulfur capacity and efficient hydrogen sulfide removal effect is achieved.

CN119819097APending Publication Date: 2025-04-15THE 718TH RES INST OF CHINA STATE SHIPBUILDING CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411714314.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The vulcanization rate of existing copper oxide desulfurizers gradually slows down at room temperature, and the vulcanization reaction is limited to the surface, and the metal ions inside the particles cannot be effectively utilized, resulting in low sulfur capacity.

Method used

The chlorine-doped copper composite is used as a desulfurizer. By reacting copper chloride with metal powder (such as zinc powder and iron powder), a chlorine-doped copper composite is formed. CuO is reduced to Cu+ and reacted with S2- to expose the metal ions inside the particles, achieving the in-depth vulcanization reaction.

Benefits of technology

The sulfur capacity of the desulfurizer and the removal efficiency of hydrogen sulfide are improved, the formation of a dense CuS film is avoided, and the metal ions inside the desulfurizer can be made more fully utilized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819097A_ABST
    Figure CN119819097A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of air purification, and particularly relates to a doped copper compound desulfurizer and a preparation method and application thereof. The preparation method comprises the following steps: step 1, preparing a copper chloride solution; 2, metal powder is added into the copper chloride solution, and standing is carried out after stirring; filtering or centrifuging to obtain a precipitate, and washing and drying to obtain the desulfurizing agent. Wherein the metal powder is selected from at least one of zinc powder, iron powder and aluminum powder, and the ratio of the amount of substance of the copper chloride to the amount of substance of the metal powder is (0.2-1): 1. The desulfurizing agent is a chlorine-doped copper compound, in the desulfurizing process, due to the existence of Cl <->, CuO in the copper compound is reduced into Cu < + >, compact CuS is not formed, the Cu < + > obtained through reduction and a small amount of CuO react with S < 2->, metal ions in a shell layer are exposed, and hydrogen sulfide continues to be removed, so that the desulfurizing agent is high in sulfur capacity and high in hydrogen sulfide removal efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of air purification, and in particular relates to a doped copper composite desulfurizer and a preparation method and application thereof. Background Art

[0002] H 2 As one of the indoor air pollutants, sulfur is mainly produced by human metabolism and the decomposition of kitchen waste, and exists in kitchens, bathrooms and sewers. Long-term exposure to low concentrations of sulfur can lead to 2 S in the air can cause nausea, headache and other symptoms. Inhalation of high concentrations (> 100 ppm) of H 2 After S, H 2 S can cause cell asphyxiation and myocardial hypoxia. When higher concentrations of H 2 S can directly lead to death. For workers in confined spaces with poor ventilation, it is urgent to take appropriate measures to remove H2 in the air. 2 S.

[0003] In recent years, with the rapid development and application of fuel cells and the demand for indoor air purification, room temperature desulfurizers have received more and more attention. At room temperature, hydrogen sulfide can chemically adsorb with metal cations in metal oxide desulfurizers, so hydrogen sulfide can be reduced to a very low concentration through the chemical reaction between hydrogen sulfide and metal oxides. Among them, copper oxide is a hot topic in the research of desulfurizers.

[0004] However, when copper oxide reacts with hydrogen sulfide at room temperature, the sulfidation rate slows down significantly with the extension of time, and only the outermost metal cations on the surface of the copper oxide particles are sulfided to form a dense CuS film. In addition, due to the limitation of the solid phase transfer rate, the sulfidation reaction cannot penetrate into the interior of the particles, which greatly reduces the sulfur capacity of the desulfurizer, resulting in these copper oxides being unable to effectively play a desulfurization role.

[0005] In this regard, small-grained copper oxide nanoparticles have been further synthesized in the art to increase the surface contact active sites to improve the utilization rate of copper oxide. Azzam SA, Alshafei FH, Ghosh R, Biswas AN, Sautet P, et al. Effects of morphology and surface properties of copper oxide on removal of hydrogen sulfide from gaseous streams. Ind Eng Chem Res 2019; 58: 18836-47 discloses a copper oxide desulfurizer, which uses 5nm grain size copper oxide as the desulfurization active component, but has the disadvantages of complex preparation process and high cost, and also cannot fundamentally improve the solid phase transfer rate, that is, the sulfidation reaction will still form a dense CuS film, and the metal ions inside the desulfurizer cannot be further better utilized.

[0006] Therefore, how to provide a low-cost desulfurizer that can fully utilize the metal ions inside the desulfurizer, avoid the formation of a dense film on the surface, and further improve the sulfur capacity is a technical problem that needs to be solved in this field. Summary of the invention

[0007] In view of the defects in the prior art, the present invention provides a doped copper composite desulfurizer and its preparation method and application. The desulfurizer is a chlorine-doped copper composite. During the desulfurization process, due to Cl - In the presence of CuO, the Cu complex is reduced to Cu + , no dense CuS is formed, and the reduced Cu + and a small amount of CuO and S 2- The desulfurizer reacts and exposes the metal ions inside the shell layer to continue removing hydrogen sulfide. Therefore, the desulfurizer has a high sulfur capacity and a high efficiency in removing hydrogen sulfide.

[0008] Specifically, the present invention provides the following technical solutions:

[0009] A method for preparing a doped copper composite desulfurizer comprises the following steps:

[0010] Step 1: Prepare copper chloride solution;

[0011] Step 2: adding metal powder to the copper chloride solution, stirring and then standing; filtering or centrifuging to obtain a precipitate, washing and drying to obtain the desulfurizing agent;

[0012] The metal powder is selected from at least one of zinc powder, iron powder and aluminum powder, and the molar ratio of cupric chloride to the metal powder is (0.2-1):1.

[0013] Preferably, in step 1, the concentration of copper chloride in the copper chloride solution is 0.02-0.1 mol / mL.

[0014] Preferably, in step 2, the metal powder is at least one of zinc powder and iron powder. The metal powder selected from zinc powder, iron powder and aluminum powder is added to reduce copper chloride to a copper complex; at the same time, compared with aluminum powder, the redox reaction of zinc powder and iron powder with copper chloride is more thorough.

[0015] Preferably, in step 2, the molar ratio of cupric chloride to metal powder is (0.8-1):1.

[0016] Preferably, in step 2, the stirring time is 30 min to 120 min;

[0017] And / or, the stirring is ultrasonic stirring.

[0018] Preferably, in step 2, the standing time is 60 min to 180 min.

[0019] Preferably, in step 2, the drying is vacuum drying at 50° C. to 70° C. for 6 h to 8 h.

[0020] The present invention also provides a doped copper composite desulfurizer, which is prepared by the above preparation method.

[0021] The present invention also provides application of the doped copper composite desulfurizer in removing hydrogen sulfide from gas.

[0022] The beneficial effects achieved by the present invention are:

[0023] (1) The present invention provides a doped copper composite desulfurizer, the crystal phase composition of which is mainly composed of metal Cu, and a small amount of Cu 2 O and CuO; its surface is mainly CuO, with a small amount of Cu 2 O and Cl - Among them, copper complexes have a high reactivity to hydrogen sulfide, due to Cl - In the presence of + , no dense CuS is formed, and the reduced Cu + and a small amount of CuO and S 2- The sulfurization reaction is not limited to the outermost surface, but can extend to the inside of the particle, eventually forming Cu 31 S 16 , greatly improving the utilization rate of copper ions, thereby greatly improving the desulfurization capacity of the material.

[0024] (2) The doped copper composite desulfurizer provided by the present invention can achieve efficient purification of hydrogen sulfide at room temperature, so it can be used for purification of hydrogen sulfide in the air and hydrogen sulfide in industrial processes, and has a good application prospect.

[0025] (3) The doped copper composite desulfurizer provided by the present invention further ensures that the prepared desulfurizer has a high desulfurization capacity by optimizing the preparation conditions such as raw material concentration, ratio, reaction time, etc.

[0026] (4) The doped copper composite desulfurizer provided by the present invention has mild preparation conditions, simple operation, and is suitable for industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the XRD diagram of the desulfurizer prepared in Example 2 in Test Example 1.

[0028] Figure 2 This is the XPS spectrum (Cu2p) of the desulfurizer prepared in Example 2 in Test Example 1.

[0029] Figure 3 The XPS spectrum (Cl2p) of the desulfurizer prepared in Example 2 in Test Example 1 is

[0030] Figure 4 The SEM morphology and EDS spectrum of the desulfurizer prepared in Example 2 in Test Example 1 are shown.

[0031] Figure 5 This is the XRD diagram of the desulfurizer prepared in Example 2 after reaction in Test Example 2.

[0032] Figure 6 This is the XPS spectrum (S2p) of the desulfurizer prepared in Example 2 after reaction in Test Example 2. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention is clearly and completely described below. The following embodiments are used to illustrate the present invention but are not used to limit the scope of the present invention. The methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels or prepared according to literature unless otherwise specified.

[0034] In the following examples, the metal powders used are all micron-sized powders.

[0035] Example 1

[0036] A method for preparing a doped copper composite desulfurizer, the method steps are as follows:

[0037] (1) At room temperature, 10 g of copper chloride dihydrate powder (CuCl 2 ·2H 2 O) was added into 100 mL of deionized water and ultrasonically treated for 20 min to obtain a cupric chloride solution;

[0038] (2) 19 g of zinc powder was added to the copper chloride solution, the molar ratio of copper chloride to zinc powder was 0.2:1, and ultrasonic stirring was performed for 60 min, and the solution was allowed to stand for 60 min and filtered. The filtered solid was first washed three times with deionized water, then washed once with anhydrous ethanol, and then vacuum dried at 70° C. for 6 h to obtain the desulfurizer.

[0039] Example 2

[0040] A method for preparing a doped copper composite desulfurizer, the method steps are as follows:

[0041] Step (1) is the same as step (1) of Example 1;

[0042] Step (2) adding 3.3 g of iron powder to the copper chloride solution, the molar ratio of copper chloride to iron powder being 1:1, ultrasonically stirring for 120 min, standing for 60 min, filtering, and washing the filtered solid three times with deionized water, then washing once with anhydrous ethanol, and then vacuum drying at 60 ° C for 6 h to obtain the desulfurizer.

[0043] Example 3

[0044] A method for preparing a doped copper composite desulfurizer, the method steps are as follows:

[0045] Step (1) is the same as step (1) of Example 1;

[0046] Step (2) adding 2.6 g of aluminum powder to the copper chloride solution, the molar ratio of copper chloride to aluminum powder is 0.6:1, ultrasonic stirring for 30 min, standing for 120 min, filtering, washing the filtered solid three times with deionized water, washing once with anhydrous ethanol, and then vacuum drying at 50 ° C for 7 h to obtain the desulfurizer.

[0047] Test Example 1

[0048] The desulfurizers prepared in Examples 1 to 3 were observed by X-ray diffractometer (XRD). Taking the test result of the desulfurizer prepared in Example 2 as an example, the XRD diagram is as follows: Figure 1 As shown in the figure, it can be clearly seen that the main crystalline component of the prepared desulfurizer is Cu (JCPDS No.04-0836), and a small amount of Cu 2O (JCPDS No. 05-0667) and CuO (JCPDS No. 45-0937); Similarly, Examples 1 and 3 have the same results, the main crystalline phase component is Cu, and a small amount of Cu 2 O and CuO.

[0049] Then, the desulfurizers prepared in Examples 1 to 3 were tested by X-ray photoelectron spectroscopy (XPS). Taking the test result of the desulfurizer prepared in Example 2 as an example, its XPS graph (Cu 2p, Cl 2p) is as follows: Figure 2 and Figure 3 As shown, it can be seen that the Cu 2+ Derived from CuO, Cu + Derived from Cu 2 O, it can be seen that the surface is composed of CuO and Cu 2 O, and contains a small amount of Cl - Similarly, Examples 1 and 3 have similar test results, indicating that the surfaces of the desulfurizers prepared in Examples 1 and 3 are composed of CuO and Cu 2 O, and contains a small amount of Cl - .

[0050] Finally, the desulfurizers prepared in Examples 1 to 3 were tested by energy dispersive X-ray spectrometer (EDS). Taking the test result of the desulfurizer prepared in Example 2 as an example, the EDS graph is as follows: Figure 4 As shown, it can be seen that the Cu, O and Cl elements on the surface of the desulfurizer are uniformly dispersed on the surface of the desulfurizer, and the atomic percentage (at%) of the Cl element is 0.13%; similarly, Examples 1 and 3 have similar test results, indicating that the Cu, O and Cl elements on the surface of the desulfurizer prepared in Examples 1 and 3 are uniformly dispersed on the surface of the desulfurizer, and the atomic percentage (at%) of the Cl element is about 0.1%.

[0051] Test Example 2

[0052] The desulfurization performance of the desulfurizers prepared in Examples 1 to 3 on hydrogen sulfide removal was tested, and the testing method was as follows:

[0053] 0.2 g of the desulfurizers prepared in Examples 1 to 3 were respectively loaded into reaction tubes with a diameter of 0.65 mm, and hydrogen sulfide (H2O) was introduced into the reaction tubes from the gas inlet. 2 S) and nitrogen, the flow rate of the mixed gas was 65 mL / min, and the H 2 The concentration of S is 1000 ppm; when the H 2 When the concentration of S reaches 100 ppm, the test is stopped. 2S) concentration was measured by sulfur analyzer; the desulfurization agent prepared in Examples 1 to 3 was recorded in the test to reduce the H in the mixed gas 2 The time (t) when the concentration of S decreases to 1000 ppm, the sulfur capacity of the desulfurizers prepared in Examples 1 to 3 is calculated according to formula (I), and the sulfur capacity calculation results are shown in Table 1.

[0054] The sulfur analyzer is a sulfur analyzer of model TY-2000-TS2 produced by Southwest Chemical Research and Design Institute Co., Ltd.

[0055]

[0056] In the formula, m is the amount of desulfurizer, g; Q is the flow rate of mixed gas, L / min; ρ is H 2 S mass density, mg / L; C inlet —H 2 S inlet concentration, L / L; C outlet —H 2 S is the outlet concentration, L / L; t is the reaction time, min.

[0057] Table 1 Sulfur content of the desulfurizers prepared in Examples 1 to 3

[0058] Desulfurization agent Sulfur capacity (mg / g) Example 1 168.2 Example 2 182.6 Example 3 172.4 Comparison reference 120

[0059] The reference data in Table 1 are from the literature Azzam SA, Alshafei FH, Ghosh R, Biswas AN, Sautet P, et al. Effects of morphology and surface properties of copper oxide on the removal of hydrogen sulfide from gaseous streams[J]. Ind Eng Chem Res 2019; 58: 18836-47, page 18842 Figure 4 The data recorded in the document are the same as those in the present application. The gas flow rate is 65 mL / min. The H in the mixed gas before the test is 2 The concentration of S was 1000 ppm, and the end point of the reaction was H 2 When the S concentration reaches 1000 ppm, the test is terminated.

[0060] It can be seen from Table 1 that the desulfurizers prepared in Examples 1 to 3 have higher sulfur capacities, all higher than the control data, and Example 2 has the largest sulfur capacity, which is about 1.5 times the reference data. It can be seen that the desulfurizer prepared in the present invention has a good removal effect on hydrogen sulfide.

[0061] After the desulfurization test, the desulfurizer of Example 2 after the reaction was tested and analyzed by X-ray diffractometer (XRD) to clarify the crystal phase composition of the desulfurizer after the desulfurization reaction. The XRD diagram of the desulfurizer after the reaction is as follows: Figure 5 As shown, from Figure 5 It can be seen that the crystal phase components except Cu, Cu 2 O, CuO, and the sulfide product Cu 31 S 16 (JCPDS No.34-0660). The desulfurizer of Example 2 after the reaction was tested and analyzed by X-ray photoelectron spectroscopy (XPS) to clarify the valence state of sulfur on the desulfurizer after the desulfurization reaction. The S2p diagram of the desulfurizer after the reaction is as follows: Figure 6 As shown, from Figure 6 It can be seen that the sulfur on the desulfurizer exists in three forms, namely S 2- , S and SO 4 2- , S 2- It is the main sulfide product.

[0062] Although the present invention has been described in detail above by general description, specific implementation methods and experiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.

Claims

1. A method for preparing a doped copper composite desulfurizer, characterized in that: The following steps are involved: Step 1: Prepare copper chloride solution; Step 2: Add metal powder to the copper chloride solution, stir and then let stand; Filter or centrifuge to obtain a precipitate, and wash and dry it to obtain the desulfurizing agent; The metal powder is selected from at least one of zinc powder, iron powder and aluminum powder, and the molar ratio of cupric chloride to the metal powder is (0.2-1):

1.

2. The preparation method according to claim 1, characterized in that: In step 1, the concentration of cupric chloride in the cupric chloride solution is 0.02-0.1 mol / mL.

3. The preparation method according to claim 1 or 2, characterized in that: In step 2, the metal powder is at least one of zinc powder and iron powder.

4. The preparation method according to claim 1 or 2, characterized in that: In step 2, the molar ratio of cupric chloride to metal powder is (0.8-1):

1.

5. The preparation method according to claim 1 or 2, characterized in that: In step 2, the stirring time is 30 min to 120 min; And / or, the stirring is ultrasonic stirring.

6. The preparation method according to claim 1 or 2, characterized in that: In step 2, the standing time is 60 min to 180 min.

7. The preparation method according to claim 1 or 2, characterized in that: In step 2, the drying is vacuum drying at 50° C. to 70° C. for 6 h to 8 h.

8. A doped copper composite desulfurizer, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 7.

9. Use of the doped copper composite desulfurizer according to claim 8 in removing hydrogen sulfide from gas.